Synthesis of Novel 7-Phenyl-2,3-Dihydropyrrolo[2,1-b]Quinazolin-9(1H)-ones as Cholinesterase Inhibitors Targeting Alzheimer’s Disease Through Suzuki–Miyaura Cross-Coupling Reaction - Davron Turgunov; Lifei Nie; Azizbek Nasrullaev; Zarifa Murtazaeva; Bianlin Wang; Dilafruz Kholmurodova; Rustamkhon Kuryazov; Jiangyu Zhao; Khurshed Bozorov; Haji Akber Aisa (Molecules)
An important field of research in medicinal and organic chemistry involves halogen-containing heterocyclic synthones, which form the backbone of more complex organic compounds. This study aimed to design and synthesize 28 novel derivatives of 7-aryl-2,3-dihydropyrrolo[2,1-b]quinazolin-9(1H)-one. The derivatives were created from 7-bromoquinoline intermediates to evaluate their potential as cholinesterase inhibitors for treating neurodegenerative diseases such as Alzheimer’s disease. The conditions for the Suzuki–Miyaura cross-coupling reaction were optimized to improve yield and purity. The derivatives were evaluated for their anticholinesterase activity using Ellman’s method, revealing that it most effectively inhibited cholinesterase within the micromolar range. 7-(3-Chloro-4-fluorophenyl)-2,3-dihydropyrrolo[2,1-b]quinazolin-9(1H)-one derivative exhibited the highest inhibitory potency, with an IC50 value of 6.084 ± 0.26 μM. Additionally, molecular dynamics simulations provided insight into how this lead compound interacts with the enzyme, suggesting its potential as a drug candidate for Alzheimer’s disease.